Corporate innovation, likelihood to be acquired, and takeover premiums - (Jennifer) Wu, Szu-Yin; Chung, Kee H. (Journal of Banking & Finance, 2019)
We analyze the effect of a firm's innovation activities on its likelihood to be acquired and the takeover premium using a large sample of M&A transactions. We show that firms with larger innovation outputs and R&D investments are more likely to be acquired, receive unsolicited bids, and receive multiple bids. The takeover premium increases with the target firm's innovation output, and this positive relation is stronger when there are more competing bidders, when acquiring firms’ product markets are competitive, and when technological proximity is lower in the acquiring firms’ industry. Both the acquirer's cumulative abnormal return around the announcement date and post-acquisition operating performance are positively related to the target firm's innovation output and R&D spending.